Advances in Iodine(III)‐Mediated Halogenations: A Versatile Tool to Explore New Reactivities and Selectivities. Issue 26 (8th April 2016) - Arnold, Andreas M.; Ulmer, Anna; Gulder, Tanja
Abstract: Within the repertoire of organic chemical transformations, the halogenation of substrates is among the most versatile, reliable, and broadly applicable reactions. Although a multitude of different methods are known today, there is still a huge demand for novel and, in particular, catalytic halogenation methods that exhibit new reactivities and selectivities. The class of hypervalent iodanes meets exactly these needs and thus offers a great opportunity to fuel this highly desirable direction within the field of halogenation chemistry. This Concept gives a short overview of recent examples focusing on selective and/or mechanistically unusual halogenations. Abstract : For your I III s only : Oxidative halogenations triggered by hypervalent iodine(III) compounds often exhibit unusual reactivities and excellent selectivities. This often makes them an interesting alternative to the common electrophilic halogenation agents. The recent developments in this field are discussed with special focus on the new opportunities offered by halogen iodanes.